Does restoration of a habitat‐forming seaweed restore associated faunal diversity?. Issue 1 (26th October 2015) - Marzinelli, Ezequiel M.; Leong, Martin R.; Campbell, Alexandra H.; Steinberg, Peter D.; Vergés, Adriana
Abstract : Declines of habitat‐forming organisms in terrestrial and marine systems can lead to changes in community‐wide biodiversity. The dominant habitat‐forming macroalga Phyllospora comosa (Fucales) went locally extinct along the metropolitan coastline of Sydney in the 1980s. However, the consequences of that disappearance to the associated faunal diversity in these habitats, and whether Phyllospora is ecologically redundant with respect to the biodiversity it supports, are not known. Efforts are underway to restore Phyllospora, and the capacity to enhance local biodiversity is an important component of the rationale for restoration. We compared epifaunal diversity (abundances and composition) between Phyllospora and two other co‐occurring habitat‐forming algae, the kelp Ecklonia radiata and the fucoid Sargassum vestitum, and determined whether Phyllospora transplanted to Sydney developed different epifaunal communities than undisturbed thalli and controls. Where the 3 species naturally co‐occurred, Phyllospora supported different abundances of taxa than Ecklonia and Sargassum, as well as different composition at finer scales, which suggests that this species is not completely redundant and that its disappearance may have affected local biodiversity. Similarly, assemblages on transplanted Phyllospora differed from those on Ecklonia and Sargassum at restored sites, but did not always resemble assemblages from extant natural Phyllospora populations, even 18 months after transplantation. These experiments indicate that restoration of key habitat‐forming seaweeds not only recovers the algal species but also reduces risks of losing habitat diversity for epifauna and their consumers. However, restoration of all the original biodiversity associated with these seaweeds can be a difficult, complex, and long‐term process.